Analisis Proksimat Cookies dari Tepung Sukun (Artocarpus altilis) dan Tepung Buah Naga Merah (Hylocereus polyrhizus): Proximate Analysis of Cookies from Breadfruit Flour (Artocarpus altilis) and Red Dragon Fruit Flour (Hylocereus polyrhizus) - Putri Diah Wulandari; Andi Tenri Kawareng; Islamudin Ahmad (Jurnal Sains dan Kesehatan, 2023)
The prevalence of diabetes mellitus in Indonesia has increased from year to year, so it is necessary to make efforts to control diabetes mellitus. One of the efforts that can be done is food arrangement with a high-fibre diet. Breadfruit and red dragon fruit are foods with high fibre content. Cookies made from breadfruit flour and red dragon fruit flour have the potential to be used as a snack for diabetics. This research aims to determine the nutritional content of cookies made from breadfruit flour and red dragon fruit flour. The results from the test is water content 4.51%, total ash content 5%, acid insoluble ash content 0.34%, glucose content 1.52%, fat content 22.65%, protein content 11.65%, carbohydrate content 56.19%, and fibre content 21.5%. Cookies made from breadfruit flour and red dragon fruit have a high fibre content so that they can be used as an alternative snack for diabetics. Keywords: Breadfruit, Red dragon fruit, Diabetes mellitus Abstrak Prevalensi diabetes mellitus di Indonesia mengalami peningkatan dari tahun ke tahun, sehingga perlu dilakukan upaya pengendalian diabetes mellitus. Salah satu upaya yang dapat dilakukan yaitu dengan pengaturan makan dengan cara diet tinggi serat. Buah sukun dan buah naga merah merupakan pangan dengan kandungan serat yang tinggi. Cookies berbahan dasar tepung sukun dan tepung buah naga merah berpotensi untuk dijadikan makanan selingan bagi penderita diabetes mellitus. Penelitian ini bertujuan untuk mengetahui kandungan gizi pada cookies berbahan dasar tepung sukun dan tepung buah naga merah. Hasil dari pengujian yang dilakukan, diperoleh kadar air 4,51%, kadar abu total 5%, kadar abu tidak larut asam 0,34%, kadar glukosa 1,52%, kadar lemak 22,65%, kadar protein 11,65%, kadar karbohidrat 56,19%, dan kadar serat 21,5%. Cookies berbahan dasar tepung sukun dan buah naga merah memiliki kandungan serat yang tinggi sehingga dapat dijadikan alternatif makanan selingan bagi penderita diabetes mellitus. Kata Kunci: Buah sukun, Buah naga merah, Diabetes Mellitus